2003
DOI: 10.1177/0261018303023002007
|View full text |Cite
|
Sign up to set email alerts
|

Articulating Gender in the Context of ICTs in Health Care: The Case of Electronic Patient Records in the Maternity Services

Abstract: The article explores the articulation of gender in the context of information and communication technologies (ICTs) in health care. It explores how gender symbolism, gender structures and gender identities combine to produce what may be perceived as `resistance' to the development of electronic patient records (EPRs) in the maternity services. In particular, midwives define their work in opposition to computers, seeing IT work as antithetical to the core `woman-centred' philosophy of midwifery. The article arg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 8 publications
(7 reference statements)
0
13
0
Order By: Relevance
“…Technology is represented as “other” to the real work of midwives and the more holistic care of being with the woman [47]. Kennedy and Shannon’s exploration of the process of midwifery care revealed how midwives achieved balance between low and high technological environments and perceived themselves as “instruments” of care through their presence with the woman [48].…”
Section: Discussionmentioning
confidence: 99%
“…Technology is represented as “other” to the real work of midwives and the more holistic care of being with the woman [47]. Kennedy and Shannon’s exploration of the process of midwifery care revealed how midwives achieved balance between low and high technological environments and perceived themselves as “instruments” of care through their presence with the woman [48].…”
Section: Discussionmentioning
confidence: 99%
“…As Doolin (2004) explains within information system architecture '[s]ome activities are given existence and attention while others remain unrecognized, enabling managerial knowledge to make stronger truth claims (Boland & Schultze 1996) and engendering compliance in those subject to such scrutiny' (p. 345). At least, in principle, as Doolin (2004) and others (Wilson 2002;Henwood & Hart 2003) have shown, professional resistance to using information systems may result in modified outcomes and disruption to managerial -professional power relations.…”
Section: Ict Disruptionsmentioning
confidence: 99%
“…Henwood and Hart, 56 for example, conducted a large, multisite case study of the introduction of electronic records in maternity units from the perspective of midwives. They found that in fewer than half of the units had midwives been consulted at all about the nature of their work or the design of the IT system.…”
mentioning
confidence: 99%
“…So all this hi-tech stuff is just not what I think it's about. Senior midwife; p. 257 56 Having first positioned the ICT as 'masculine' and as interfering with the 'normal' process of birth, this interviewee went on to distance herself (and midwifery in general) from the low-status administrative work of 'data entry'. In her symbolic world, technology was either about ethereal, unreal aspects of care or not about care at all.…”
mentioning
confidence: 99%